Perilaku Keagamaan Kemaja Kristen Konsumen Miras Di GPIBK jemaat Imanuel Taepa - Aderino Kaloan; Junni Yokiman; Oscar Sopang (Institut Agama Kristen Negeri Kupang, 2022)
The fundamental problem of this scientific work is the Religious Behavior of Christian Teens Alcohol Consumers at the GPIBK of the Imanuel Taepa Congregation and the influence of Christian values ??on adolescent alcohol consumers in the GPIBK of the Taepa Congregation. The aims of this study include: to find out how the religious behavior of Christian teenagers who drink alcohol at GPIBK Imanuel Taepa congregation and how the influence of Christian values ??on adolescent alcohol consumers. In this study, the authors examine the problem using qualitative methods using a case study approach for field exploration with the aim of gaining more knowledge in a situation or a case. And the population that chose the author was 17 people, 14 teenagers, 2 councilors, 1 person and the sample was 7 people. The author uses several sources such as books, journals, and other media as sources of information. As for the results of the study, the authors found that the religious behavior of Christian teenagers who consume alcohol in terms of loving God, loving others and loving themselves is not reflected in their behavior as Christian teenagers. Because of the lack of influence of Christian values ??given by parents and even the Church. For this reason, parents and the church must play an active role in teaching Christian values ??and being an example for teenagers.